Новый вид ацератерия из раннего сармата Украины - Короткевич, Е.Л. (Вестник зоологии, 1974)
A new species — Aceratherium belaevi sp. n. is described from the Lower Sarmatian sands near the vil. Oselivka of the Kelmentsian district, Chernovtsy region of the Ukrainian SSR. Main features of the species are as follows: small size, a comparatively short diastema, shortened raw of premolars, the absence of basal formations on the man¬dible teeth.